Enhancement of Aqueous Solubility and Dissolution Rate of Etoricoxib by Solid Dispersion Technique - AlKhalidi, Mustapha M.; J. Jawad, Fatima (Iraqi Journal of Pharmaceutical Sciences, 2020)
Etoricoxib (EXB) is a highly selective cox-2 inhibitor which belongs to the non-steroidal anti-inflammatory drug (NSAID). EXB is a class II drug according to the biopharmaceutical classification system (BCS), which possess a very low aqueous solubility in water. In the present study, many trials were made to improve the aqueous solubility and dissolution rate of EXB by solid dispersion technique.Eighteenth EXB formulas were formulated as a solid dispersion using a variety of hydrophilic polymers (as carriers) including poloxamer 407 (PXM 407), poloxamer 188 (PXM 188) and polyethylene glycol 4000 (PEG 4000) at different drug: polymer ratios (1:1, 1:3 and 1:5). These formulas were prepared by two methods; solvent evaporation and fusion method. The prepared formulas were evaluated for practical yield percent (PY %), drug content, saturated solubility and release rate, Fourier transforms infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and powder x-ray diffraction (PXRD).It was found that the solubility was affected by the polymer type and the method of preparation. The polymers (as carriers) used to prepare EXB- solid dispersion showed improvement in the solubility in the following descending order; PXM 407>PXM 188> PEG 4000. The optimum formula (SD15) composed of the drug: PXM 407 at a ratio of 1:5 was prepared by solvent evaporation showed 7.76 folds (676.40%) solubility improvement as compared to pure EXB. The optimum formula showed a release rate of 99.8% through the first 15 min. The advance characterization of the selected formula indicated the possible transformation of the drug to the amorphous state.Keywords: EXB, Solid dispersion, PXM 407, PXM 188, PEG 4000.